2004
DOI: 10.1210/me.2004-0017
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Thyrotropin-Releasing Hormone Receptor 1-Deficient Mice as an Animal Model of Central Hypothyroidism

Abstract: To provide an animal model of central hypothyroidism, mice deficient in the TRH-receptor 1 (TRH-R1) gene were generated by homologous recombination. The pituitaries of TRH-R1-/- mice are devoid of any TRH-binding capacity, demonstrating that TRH-R1 is the only receptor localized on TRH target cells of the pituitary. With the exception of some retardation in growth rate, TRH-R1-/- mice appear normal, but compared with control animals they exhibit a considerable decrease in serum T(3), T(4), and prolactin (PRL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 52 publications
5
44
0
Order By: Relevance
“…The importance of the effects of TRH on TSH glycosylation and activity (Weintraub et al 1989) has been demonstrated by comparing the phenotypes of TRH-KO, THRb-KO, and the double mutant. Increased TSH serum levels but reduced TSH bioactivity accounts for the low circulating T 4 concentration (Nikrodhanond et al 2006), similar to that observed in humans with hypothalamic hypothyroidism (Beck-Peccoz et al 1985), or in TRHR1 K/K mice that have normal TSH levels but low circulating T 3 and T 4 concentrations (Rabeler et al 2004). D1-, D2-, and D1D2-KO show compensatory mechanisms in the interplay between hypophysiotropic TRHergic neurons, pituitary TSH expression and release, which in combination maintain serum levels of T 3 stable despite altered serum concentrations of T 4 and TSH (Abdalla & Bianco 2014, Galton et al 2014.…”
Section: Regulation Of Hpt Axis Activity By Trh and Negative Feedbacksupporting
confidence: 62%
See 4 more Smart Citations
“…The importance of the effects of TRH on TSH glycosylation and activity (Weintraub et al 1989) has been demonstrated by comparing the phenotypes of TRH-KO, THRb-KO, and the double mutant. Increased TSH serum levels but reduced TSH bioactivity accounts for the low circulating T 4 concentration (Nikrodhanond et al 2006), similar to that observed in humans with hypothalamic hypothyroidism (Beck-Peccoz et al 1985), or in TRHR1 K/K mice that have normal TSH levels but low circulating T 3 and T 4 concentrations (Rabeler et al 2004). D1-, D2-, and D1D2-KO show compensatory mechanisms in the interplay between hypophysiotropic TRHergic neurons, pituitary TSH expression and release, which in combination maintain serum levels of T 3 stable despite altered serum concentrations of T 4 and TSH (Abdalla & Bianco 2014, Galton et al 2014.…”
Section: Regulation Of Hpt Axis Activity By Trh and Negative Feedbacksupporting
confidence: 62%
“…This discrepancy may be explained by CART which inhibits PRL release and its expression is upregulated in hypophysiotropic TRH neurons by cold but not by suckling (Sánchez et al 2007). TRH and TRHR1 KO mice have shown that while TRH is necessary to sustain PRL secretion during lactation, pups from KO dams grow normally, suggesting that TRH is not essential for suckling-induced PRL release (Rabeler et al 2004.Contrary to data showing that anterior pituitary PPII does not regulate the response of thyrotroph response to TRH, there is evidence that in lactotrophs the intensity of TRH action is under PPII control. PPII is expressed in lactotrophs and its knockdown or inhibition enhances TRH-induced PRL release (Cruz et al 2008).…”
mentioning
confidence: 84%
See 3 more Smart Citations